2020
DOI: 10.1101/2020.06.09.20116806
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Pre exposure Hydroxychloroquine Prophylaxis for COVID-19 in healthcare workers: a retrospective cohort

Abstract: Background: While several trials are ongoing for treatment of COVID-19, scientific research on chemoprophylaxis is still lacking even though it has potential to delay the pandemic allowing us time to complete research on vaccines. Methods: We have conducted a cohort study amongst Health Care Workers (HCW) exposed to COVID-19 patients, at a tertiary care center in India where there was an abrupt cluster outbreak within on duty personnel. HCWs who had voluntarily taken hydroxychloroquine (HCQ) prior to exposu… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
12
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(15 citation statements)
references
References 28 publications
1
12
0
Order By: Relevance
“…This is consistent with the findings of an observational prophylaxis study involving mainly younger HCW in India. 5 Our preliminary analysis revealed a statistically significant negative correlation (slope -0.211, 95%CI -0.328-0.094, p=0.016, rho CI -1 to -0.42, confirmed independently 6 ) between treatment lag and reduction of COVID-19, reaching 49% when given within one day after exposure (RR 0.51, CI 0.176-1.46, p=0.249). The early use of HCQ is supported by mathematical modeling that considers the peaking of the viral load in the pharyngeal cavity and the effect of the drug to kill infected cells by enhancing cell-mediated immunity.…”
mentioning
confidence: 52%
“…This is consistent with the findings of an observational prophylaxis study involving mainly younger HCW in India. 5 Our preliminary analysis revealed a statistically significant negative correlation (slope -0.211, 95%CI -0.328-0.094, p=0.016, rho CI -1 to -0.42, confirmed independently 6 ) between treatment lag and reduction of COVID-19, reaching 49% when given within one day after exposure (RR 0.51, CI 0.176-1.46, p=0.249). The early use of HCQ is supported by mathematical modeling that considers the peaking of the viral load in the pharyngeal cavity and the effect of the drug to kill infected cells by enhancing cell-mediated immunity.…”
mentioning
confidence: 52%
“…Guideline panels determine the overall quality of evidence across all the critical outcomes essential based on: 1) If the quality of evidence is the same for all critical outcomes, then this becomes the overall quality of the evidence supporting the answer to the question; 2) If the quality of evidence differs and there is inconsistent results across critical outcomes, the interval quality of evidence is supplied; 3) If the quality of evidence differs and there is consistent results across critical outcomes, the lowest quality of evidence for any of the critical outcomes determines the overall quality of evidence Evidence summary A retrospective cohort study including 106 healthcare workers indicated that as for 54 health care personnel before being exposed to their first COVID-19 patients, taking pre-exposure hydroxychloroquine prophylaxis was associated with an 80.7% reduction in the risk of acquiring a SARS-CoV-2 infection (RR = 0.193; 95% CI = 0.071-0.526; P = 0.001) compared with those who were not on it. Adverse effects, mostly mild, were recorded in 29.8% of those on hydroxychloroquine prophylaxis (gastrointestinal upset: 19.1%; skin rash: 6.4%; headache: 4.3%) [11]. The quality of evidence was very low due to lack of adequate information relevant to study design, for example, co-interventions balanced across intervention groups, start time of follow-up and start of intervention for most participants and imprecision of evidence quality.…”
Section: Chemoprophylaxismentioning
confidence: 99%
“…One non-RCT [52] reported 80 patients with COVID-19 who received lopinavir-ritonavir or favipiravir (all received interferon α2b atomized inhalation). The time of positiveto-negative conversion of RT-PCR test in lopinavir-ritonavir group (n = 45) was longer than that in favipiravir group (n = 35) (median, IQR, 11 [8][9][10][11][12][13] days vs. 4 [2.5-9] days, P < 0.001), but the rate of chest imaging improvement was faster in favipiravir group (91.4% vs. 62.2%, P = 0.004). The incidence of adverse reactions in the lopinavir-ritonavir group was higher than that in favipiravir group (55.6% vs. 11.4%, P < 0.001).…”
Section: Implementation Considerationmentioning
confidence: 99%
“…One cohort study found that 38% of untreated HCWs developed COVID-19 infection compared to 7% of HCWs treated with weekly HCQ PrEP (p<0.001). 40 The second case-control study of HCWs found that four or more weekly doses of HCQ resulted in significantly less infection with SARS-CoV-2 (adjusted odds ratio 0.44, p<0.001). 41 The third study was a questionnaire-based analysis showing that HCWs who had taken a full course of HCQ PrEP (seven or more weekly doses) had significantly less infection with SARS-CoV-2 compared to those who had taken either an incomplete course or no HCQ at all (p = 0.021).…”
Section: Hydroxychloroquine Prepmentioning
confidence: 99%